If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(4-x)=x+3(x-2)
We move all terms to the left:
-2(4-x)-(x+3(x-2))=0
We add all the numbers together, and all the variables
-2(-1x+4)-(x+3(x-2))=0
We multiply parentheses
2x-(x+3(x-2))-8=0
We calculate terms in parentheses: -(x+3(x-2)), so:We get rid of parentheses
x+3(x-2)
We multiply parentheses
x+3x-6
We add all the numbers together, and all the variables
4x-6
Back to the equation:
-(4x-6)
2x-4x+6-8=0
We add all the numbers together, and all the variables
-2x-2=0
We move all terms containing x to the left, all other terms to the right
-2x=2
x=2/-2
x=-1
| 4x+x-4x=40 | | 20=166x | | m+14.2=-2.41 | | -2x+57=180 | | 3x+x+9=3x+16 | | 5.x/3-3=-7 | | 57-2x=180 | | 6(2x+1)=3(x+8) | | 3(2x-1)=0.5(x+6) | | 4x+5=11+3x | | 5x–18=7 | | 8x^2+8x=424 | | 11m=8m-6 | | -45x-20=20x-12 | | 14x+6-5x=34+5x+19 | | x*5-24=31 | | 10(3.14)*360/10(3.14)=x | | 9/11=x/661 | | -2y-4=2 | | 6(x-3)-2-(x+4)=2 | | 2x+3x-14+(x+5)=39 | | -2(4+2x)=4x | | m/9+3=7 | | 12r=5r+7 | | 2(x+5)-12=5+x | | -5x+3=-2x+5-3x | | 36=g2 | | 15x+-15=180 | | t2=200 | | a/4+8=10a= | | 44-2m=38 | | 19+5.5h=10+6.75h |